2012
DOI: 10.1016/j.physa.2011.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Group chase and escape with conversion from targets to chasers

Abstract: We are studying the effect of converting caught targets into new chasers in the context of the recently proposed 'group chase and escape' problem. Numerical simulations have shown that this conversion can substantially reduce the lifetimes of the targets when a large number of them are initially present. At the same time, it also leads to a non-monotonic dependence on the initial number of targets, resulting in the existence of a maximum lifetime. As a counter effect for this conversion, we further introduce s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…The motion of each particle is similar to that in Refs. [8,9]. In one trial, we choose one of the particles and move the particle.…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The motion of each particle is similar to that in Refs. [8,9]. In one trial, we choose one of the particles and move the particle.…”
Section: Modelmentioning
confidence: 99%
“…When the area in which the target searches for the chasers is wider than the area in which the chasers search for the target, the time dependence changes from t to t 1.65 . Recently, Kamimura and co-workers used a simple model and studied group chase and escape [8][9][10]. In the studies, the system consists of two types of species: one is a group of chasers, which try to catch the nearest target, and the other is a group of targets, which escape from the nearest target.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For * sato@cs.s.kanazawa-u.ac.jp example, Nishi and coworkers studied the group chase and escapes under a conversion law [9], and we studied the group chase and escape with three species [10]. In the previous paper [8], some variations of the original model, which are valuable to study, are suggested.…”
Section: Introductionmentioning
confidence: 99%